Pancasila and the Principle of Equilibrium in Customary Law: Safeguarding the Cosmological Rights of Indigenous People - Tijow, Lusiana Margareth; Hayat, Hayat; Azlina, Tengku Elmi (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2024)
The principle of equilibrium is an ethical demand closely related to the communal mentality of customary law, encompassing moral, social, and legal values. Therefore, this research aimed to understand the application of equilibrium to the cosmological rights of indigenous and tribal people in implementing Pancasila values. Normative legal research was used with a statutory method to achieve a clear understanding of the issues discussed. The results showed that equilibrium served as a guide for creating a balance between rights and obligations realised concretely through legal and non-legal norms. Furthermore, the different rights owned by indigenous people were recognised and respected. In this context, the government needs to prioritise Pancasila values in development and pay attention to the cosmological rights of indigenous and tribal people. Customary law must address various legal issues faced by people in specific areas and uphold the fundamental rights.